EDUKASI PENCATATAN KEUANGAN SIMPAN PINJAM PKK KELURAHAN NGESREP KECAMATAN BANYUMANIK SEMARANG - Greg Anggana Lisiantara; Pancawati Hardiningsih; Ceacilia Srimindarti; Bambang Sutejo (PENA ABDIMAS : Jurnal Pengabdian Masyarakat, 2022)
The problems faced by the PKK savings and loan business in the Ngesrep sub-district, Banyumanik sub-district, Semarang city are that recording has not been carried out properly according to generally accepted principles and how to present the financial statements of the savings and loan units that are simple and more informative. This educational activity is carried out in the form of counseling and training on recording financial transactions of the savings and loan unit and consultative/assistance assistance. This community service program was attended by 25 managers of savings and loan units in the Ngesrep sub-district, Banyumanik sub-district. The results show that the savings and loan unit of the PKK has begun to apply the usual accounting principles by fixing the bookkeeping of the savings and loan unit so that it does not only meet internal information needs. The recording system is carried out through a simple account to facilitate monitoring and reporting.Keywords: Transaction recording, consultative assistance, financial reports